Creatine or vitamin D supplementation in individuals with a spinal cord injury undergoing resistance training: A double-blinded, randomized pilot trial. (4th July 2018) - Amorim, Samuel; Teixeira, Vitor Hugo; Corredeira, Rui; Cunha, Maria; Maia, Bruno; Margalho, Paulo; Pires, Joana
Abstract : Purpose: Determine whether creatine or vitamin D supplementation improves muscle strength in individuals with spinal cord injury undergoing resistance training. Methods: Thirteen male and one female with spinal cord injury, from two Portuguese rehabilitation centers, were randomized to creatine (3g daily), vitamin D (25000 IU each two weeks) or placebo group in a double-blind design. All participants performed progressive resistance training during eight weeks. The outcome measures, obtained at baseline and after intervention, included: Sum of four skinfolds; Corrected arm muscle area; Seated medicine ball throw; Handgrip strength with dynamometer; Manual wheelchair slalom test and one repetition maximum for Chest press, Triceps, Pec deck and Lat pulldown. Vitamin D levels were obtained in all participants before and after intervention. Results: 71.4% of participants had deficit values of vitamin D. The corrected arm muscle area improved significantly (p<0.05) in creatine group relatively to the control group. There was a significant correlation (p<0.05) between the one repetition maximum Pec deck and levels of vitamin D. Conclusions: Supplementation with creatine may improve muscle strength parameters in individuals with spinal cord injury. Vitamin D deficiency is highly prevalent in this population. It is recommended an initial screening of vitamin D levels at the beginning of the physical rehabilitation process.